The relationship between single-limb squat and jump-cut kinematics. Issue 5 (28th May 2022) - Scarneo-Miller, Samantha E.; Sorge, Jarrett E.; Beltz, Eleanor M.; Martinez, Jessica C.; Root, Hayley J.; Burland, Julie P.; Trojian, Thomas H.; DiStefano, Lindsay J.
ABSTRACT: No objective criteria exist for progressing athletes into cutting manoeuvres following ACL reconstruction (ACLR). The purpose of this study was to evaluate the relationship between a jump-cut task (JC) and the single-limb squat (SLS) in both ACLR and healthy controls. Case-control, laboratory based. Twenty-three participants with a history of ACLR (Age = 21 ± 3 years; Height = 174.5 ± 7.2 cm; Mass = 76.2 ± 9.9 kg) and 23 healthy controls participants (Age = 21 ± 3 years; Height = 173.8 ± 9.2 cm; Mass = 75.0 ± 10.5 kg) were included. Kinematics were collected bilaterally. Correlations between tasks were evaluated for kinematics. Independent sample t-tests were used to evaluate differences between groups for each dependent variable. Peak trunk rotation and medial knee displacement were strongly correlated (p < 0.001, r 2 = 0.63), between tasks. ACLR group performed SLS and JC tasks with less sagittal plane motion compared to healthy controls (p < 0.05). Lack of frontal and transverse plane control during SLS resulted in positions of increased lateral trunk flexion, hip adduction, and medial knee displacement during JC. The SLS may be considered for use as a clinical predictor of JC during rehabilitation following ACLR.